Prevent Diseases Before It's Too Late: Early Detection of Non-Communicable Diseases with Carotis Ultrasound at Hermon Hollo Him Church, Sentani, Jayapura Regency - Labobar, Maryam Kathrien; Astawa, Gregorius Adista Enrico; Setyarini, Kaida Irma; Rumboirusi, Ricky Lazarus; Mahu, Grace Fitriani Primasari Hau; Rante, Indra Harianto; Korwa, Irjani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Deaths from non-communicable diseases (NCDs) in the world of 17.9 million people per year are caused by cardiovascular diseases, followed by cancer, chronic respiratory diseases and diabetes mellitus with complications. In Indonesia, deaths due to NCDs reach 73% based on the World Health Organization Non Communicable Diseases Progress Monitor 2020. Therefore, this service aims to screen for non-communicable diseases through blood tests and carotid artery ultrasound which is useful for early detection of stroke and heart disease in church members, which are communities with different backgrounds. The methods used are blood tests and ultrasound of the carotid artery. The results of the examination showed that some residents were at risk of non-communicable diseases, hypertension, stroke, coronary heart disease.